EFFECTS OF HYDROPHOBIC SILICA ADDITIVES ON THE STRUCTURE AND PERFORMANCE OF PVDF MEMBRANES FOR LIQUID FILTRATION - FERNANDES, CHARLENE SHARMINI (2019)
Membrane fouling is a main challenge in most pressure driven membrane processes. Improving membrane surface characteristics plays an important role in fouling mitigation efforts.